Undermining racial justice : how one university embraced inclusion and inequality - Johnson, Matthew (Matthew James), 1983- (Histories of American education., 2020)
"In this book, Matthew Johnson focuses on the University of Michigan-an institution at the epicenter of the struggle over what racial justice should look like in practice in American higher education. In 1963, Michigan became one of the first post-secondary institutions in the United States to create an affirmative action admissions program. Since then, Michigan administrators have been on the frontlines of implementing and defending race-conscious solutions to inequality. Johnson analyzes the five-decade fight, from the early 1960s to the turn of the twenty-first century, over what racial justice should look like at the University of Michigan. He finds that, over time, the early linkage between racial equality and social and economic justice became attenuated. The rise of the language of diversity as the goal of Michigan's admissions program signaled the decline of social and economic justice as a stated or even implicit goal of admissions policy"--